2017
DOI: 10.61426/sjbcm.v4i4.567
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Investment Decisions of Pension Schemes in Kenya

Sharon Chepkoech

Abstract: This study sought to determine the factors affecting investment decisions of Pension schemes in Kenya. Its objectives were to: establish the effect of risk-return tradeoff on investment decisions of pension schemes in Kenya and determine the effect of macroeconomic factors on investment decisions of pension schemes in Kenya. It was conceptualized that investment decisions in pension schemes (dependent variable) were dependent on risk-return trade off and macroeconomic factors (the independent variables). The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In their panel study, Zhao and Sutcliffe (2021) focused on examining the factors that influence equity allocation in UK pension funds, and reported that scheme maturity, funding ratio, and time trend had the most significant impact on the allocation of assets, particularly equity allocation. Chepkoech et al (2017) conducted a study to examine the factors influencing investment decisions of pension schemes in Kenya, and the findings indicated that the risk-return tradeoff had a significant influence on the investment decisions of pension schemes in Kenya, and that fund managers carefully balance the level of risk associated with investments to ensure optimal returns, while macroeconomic factors such as interest rates, performance of capital markets, and the rate of national economic growth playing a crucial role in shaping the investment decisions of pension schemes. Wanjohi and Kariuki (2019) conducted a study in Kenya aiming at providing valuable insights to the government and stakeholders in the pension sector regarding the screening and adoption of appropriate investment policies and strategies to effectively enhance the wealth of pensioners.…”
Section: Empirical Literaturementioning
confidence: 99%
“…In their panel study, Zhao and Sutcliffe (2021) focused on examining the factors that influence equity allocation in UK pension funds, and reported that scheme maturity, funding ratio, and time trend had the most significant impact on the allocation of assets, particularly equity allocation. Chepkoech et al (2017) conducted a study to examine the factors influencing investment decisions of pension schemes in Kenya, and the findings indicated that the risk-return tradeoff had a significant influence on the investment decisions of pension schemes in Kenya, and that fund managers carefully balance the level of risk associated with investments to ensure optimal returns, while macroeconomic factors such as interest rates, performance of capital markets, and the rate of national economic growth playing a crucial role in shaping the investment decisions of pension schemes. Wanjohi and Kariuki (2019) conducted a study in Kenya aiming at providing valuable insights to the government and stakeholders in the pension sector regarding the screening and adoption of appropriate investment policies and strategies to effectively enhance the wealth of pensioners.…”
Section: Empirical Literaturementioning
confidence: 99%